Digital Inclusive Finance and Foreign Direct Investment: Regression Analysis Based on Spatial Econometric Models - Xu Yekai (International Journal of Education and Humanities, 2024)
This study investigates the relationship between digital inclusive finance (DIF) and foreign direct investment (FDI) in China, using panel data from 31 provinces, municipalities, and autonomous regions from 2011 to 2022. The research employs a dual fixed spatial Durbin model to empirically analyze the impact of DIF on FDI and its spatial effects. The primary issue addressed in the study is how DIF influences FDI, both within a region and across neighboring areas. The main objective of the research is to evaluate the spatial clustering characteristics between DIF and FDI and to determine whether DIF significantly enhances FDI levels in a region. Furthermore, the study aims to understand the "siphon effect," where DIF may attract FDI away from surrounding areas. Methodologically, the dual fixed spatial Durbin model is utilized to capture both the direct and spillover effects of DIF on FDI across regions. The study examines regional heterogeneity, particularly how the impact of DIF varies across eastern, central, and western China. The results reveal that DIF indeed has a spatial clustering distribution with FDI, which can significantly boost FDI within a region. However, it also generates a siphon effect, attracting FDI from surrounding areas. Additionally, the study highlights regional differences, with the positive effect of DIF on FDI diminishing as one moves from the eastern to the western regions. Meanwhile, the negative spatial spillover effect of DIF development on neighboring areas is significant across all regions. Based on these findings, the study recommends tailored policy interventions to address regional disparities and mitigate adverse spillover effects, ensuring balanced development across regions